PENGARUH KINERJA KEUANGAN PEMERINTAH DAERAH, PERTUMBUHAN EKONOMI, FISCAL STRESS, DAN KEPADATAN PENDUDUK TERHADAP ALOKASI BELANJA MODAL - Kusumaningrum, Enggar Bayu; Sugiyanto, Hari (EKONOMI BISNIS, 2021)
This study aims to examine the effect of financial performance, economic growth, fiscal stress, and population density on capital expenditure allocation. This research employs quantitative research methodology with multiple linear regression models. The sample used in this research is district or city in North Kalimantan. The type of data used in this study is secondary data from budget realization report and statistics Indonesia from 2013 to 2019. This study finds that independence ratio and fiscal stress are negatively associated with capital expenditure allocation. While efektivity ratio, economic growth and population density are positively associated with capital expenditure allocation. Furthermore, financial performance, economic growth, fiscal stress, and population density simultaneously effect the allocation of capital expenditure.